Functionalized covalent organic framework material as well as preparation method and application thereof
By using functionalized covalent organic frame materials on the negative electrode of metal secondary batteries, the specific capacity limit and safety hazards of traditional battery materials are solved, and higher cycle life and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411444572.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-14
AI Technical Summary
Graphite, the negative electrode material of traditional lithium-ion batteries, has approached its theoretical specific capacity limit and cannot meet the demand for high-energy density energy storage devices by new energy vehicles and portable electronic devices. Metal secondary batteries have attracted attention due to their high specific capacity and theoretical energy density, but they have problems such as side reactions, dendrite growth, safety hazards and capacity loss.
A functionalized covalent organic frame material is designed to form a side chain functionalized covalent organic frame material by introducing oxygen-containing groups and long-chain groups that capture ion functions on the COF framework. The material is loaded on metal to form a composite negative electrode, and the side chain rotation and swing pull the movement of metal ions, inducing the electrolyte to decompose to form a uniform SEI film, improving battery performance.
By functionalized covalent organic frame materials, the cycle life, electrochemical performance and safety of metal secondary batteries are improved, volume expansion and dendritic growth are slowed down, mass transfer kinetic performance of the negative electrode is enhanced, and high-speed charging is achieved.
Smart Images

Figure CN119613643A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chemical functional composite materials, and in particular to a functionalized covalent organic framework material and a preparation method and application thereof. Background Art
[0002] With the continuous advancement of science and technology and the rapid development of society, the demand for new energy vehicles and portable electronic devices is growing rapidly, and society's desire for high-energy-density energy storage devices is becoming more and more urgent. However, the research on traditional lithium-ion batteries using graphite as the negative electrode material has approached the limit of its theoretical specific capacity and cannot meet the needs of today's human beings. Therefore, scientists began to explore other high-specific-capacity energy storage devices. In recent years, metal secondary batteries using active metals such as lithium, sodium, potassium, and zinc as negative electrodes have become a research hotspot in the energy field due to their superior specific capacity and theoretical energy density, showing important research value and broad application prospects.
[0003] Although metal secondary batteries have the advantage of high energy density, there are still some urgent problems to be solved, mainly including: (1) Complex side reactions occur between highly active metals and electrolytes, consuming organic molecules and anions in the electrolyte to form a multi-component solid electrolyte interface film (SEI film), some of which have low ionic conductivity, which limits the material transfer reaction kinetics and electrochemical performance of the battery at high rates; (2) Due to the uneven current distribution, active metals tend to deposit in the form of dendrites during the charge and discharge process. At the same time, the slow metal ion transfer will accelerate the growth of metal dendrites, and the growth of dendrites may penetrate the diaphragm and contact the positive electrode, thereby causing a short circuit, leading to thermal runaway and bringing safety hazards; (3) During the charge and discharge process, the deposition and stripping of active metals causes the metal negative electrode to undergo significant volume changes, resulting in the continuous rupture and reconstruction of the original SEI film, which not only causes local ion deposition to aggravate the growth of dendrites, but also the rupture of dendrites can lead to the loss of electrical contact, thereby causing capacity loss.
[0004] Using modifying substances to modify metal electrodes, regulate the components of SEI membranes in batteries and improve the performance of SEI membranes is one direction to solve the above problems. However, what kind of substances to use to modify metal electrodes to achieve good results is a difficult problem that technicians in this field need to solve. Summary of the invention
[0005] Based on this, the purpose of the present invention is to provide a functionalized covalent organic framework material and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0006] Part I:
[0007] A functionalized covalent organic framework material, the structural formula of which is shown in Formula I:
[0008]
[0009] Wherein, X is C and / or N, and Y includes at least one of dimethyl ether, 1,2-dimethoxyethyl, 1-methoxy-2-(2-methoxyethoxy)ethyl, 1-methoxy-2-methylpropane, 1-methoxybutane and 1-methoxyheptane.
[0010] The present invention designs and introduces oxygen-containing groups and long-chain groups with ion-capturing functions into covalent organic framework materials (COF) to obtain side-chain functionalized covalent organic framework materials. Specifically, it is loaded on a metal to form a composite negative electrode and assembled into a battery. The protruding side chains on the COF skeleton can rotate and swing during the charge and discharge process, pulling metal ions to move quickly; due to the presence of the side chains, the asymmetric structure can lead to uneven distribution of electron clouds, increase the COF molecular dipole moment, thereby inducing electrolyte decomposition, forming a uniform SEI film rich in inorganic salt components (such as fluoride), etc., and improving the material transfer reaction kinetics and electrochemical performance of the battery at high rates; in addition, the SEI film rich in inorganic salt components further accelerates carrier transport and induces uniform nucleation of metal ions to avoid deposition in the form of dendrites; in addition, by designing the side chain to capture ions to fill the pores in the center of the COF ring, the problem that the vacant COF pores have no ion-conducting sites is compensated, and the space utilization rate of COF can be further increased, the volume expansion is slowed down, the capacity loss is reduced, and the electrochemical performance of the metal secondary battery such as the cycle life is improved.
[0011] Part II:
[0012] A method for preparing the functionalized covalent organic framework material as described in the first part comprises the following steps:
[0013] Mixing aldehyde molecules, amino molecules, glacial acetic acid and a first solvent, and heating to react to obtain the functionalized covalent organic framework material;
[0014] The aldehyde group molecule includes at least one of 1,3,5-tris(p-formylphenyl)benzene and 2,4,6-tris(4-formylphenyl)-1,3,5-triazine;
[0015] The amino molecules include at least one of 2,5-dimethoxyterephthaloyl hydrazide, 2,5-bis(2-methoxyethoxy)terephthaloyl hydrazide, 2,5-bis(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)terephthaloyl hydrazide, 2,5-diisobutoxyterephthaloyl hydrazide, 2,5-dibutoxyterephthaloyl hydrazide, and 2,5-bis(heptyloxy)terephthaloyl hydrazide;
[0016] The first solvent includes at least one of mesitylene, 1,4-dioxane, o-dichlorobenzene, n-butanol, methanol, pyridine, N-methylpyrrolidone, and dimethyl sulfoxide.
[0017] The method for preparing the functionalized covalent organic framework material of the present invention has the following advantages:
[0018] (1) The functionalized covalent organic framework material of the present invention is synthesized by Schiff base reaction with aldehyde molecules and functionalized amino molecules. The rich pore structure of the COF skeleton provides a fast ion transmission channel, which promotes the transport of carriers. The side chains introduced by the functionalized amino molecules can further pull the ions to move quickly by rotating and swinging during the reaction; the asymmetric side chain structure increases the molecular dipole moment, which is conducive to inducing the decomposition of the electrolyte to form a functional SEI film; the presence of dynamic imine bonds and carbon-nitrogen double bonds guide the uniform deposition of metal ions, while effectively improving the Young's modulus of the SEI film and inhibiting the volume expansion and dendrite growth of the metal negative electrode.
[0019] (2) The present invention uses aldehyde molecules and functionalized terephthalic acid dihydrazine amino molecules as monomers to synthesize COF. Due to the presence of benzene rings and skeleton carbon-nitrogen double bonds, the π electrons in the same plane form a hyperconjugated system, and the structure is extremely stable, which can maintain structural integrity during the battery charge and discharge cycle; the primary amine in the functionalized terephthalic acid dihydrazine amino molecule reacts with the aldehyde group of the aldehyde molecule through a Schiff base reaction to form a dynamic imine bond as a link, which has a high Young's modulus and self-repairing function, can effectively adapt to the volume expansion of the metal negative electrode during the charge and discharge process, and at the same time inhibit the growth of metal dendrites to prevent piercing the diaphragm and causing a short circuit.
[0020] (3) The present invention uses aldehyde molecules and functionalized terephthalic acid dihydrazine amino molecules as monomers to synthesize COF. Due to the special functionalized amino molecular monomers, protruding side chains are introduced on the COF skeleton. Since the side chains do not form a conjugated system and can rotate and swing flexibly, they can act as "ion pumps" to continuously pull ions to move quickly during the reaction. In the present invention, the pores in the center of the COF ring are filled by designing side chains to capture ions, which makes up for the problem that the vacant COF pores have no ion-conducting sites, and can further increase the space utilization of COF and effectively improve the ion conductivity. The introduced side chain groups can effectively adjust the distribution of electron density, form electron-rich regions in the COF ring to attract active metal ions to pass regularly, thereby achieving uniform distribution of active metal ions and nucleation, alleviating the growth of dendrites, and solving the problems of battery capacity attenuation and cycle life reduction caused by dendrite breakage.
[0021] (4) The present invention uses aldehyde molecules and functionalized terephthalic acid dihydrazine amino molecules as monomers to synthesize COF. Due to the presence of its side chain groups, the electron-donating groups and the asymmetric molecular structure cause the electron cloud of the COF skeleton to be unevenly distributed, resulting in an increase in the overall dipole moment of the molecule, which can effectively attract the electrolyte to decompose in a directional manner on the COF skeleton, forming a uniform SEI film rich in inorganic salt components (such as metal fluorides, etc.), reducing the nucleation barrier of active metal ions while improving ionic conductivity. Loading it on a metal to form a composite negative electrode can effectively improve the mass transfer kinetics of the negative electrode, achieve high-rate fast charging, etc., and improve the performance of metal secondary batteries.
[0022] As a preferred solution, the molar ratio of the aldehyde molecule to the amino molecule is 2:3-3.2, and the concentration of the glacial acetic acid is 6-12 mol / L; the liquid-solid ratio of the first solvent to the sum of the mass of the aldehyde molecule and the amino molecule is 1-2 mL:20 mg, and the volume ratio of the first solvent to the glacial acetic acid is 1:0.1-0.2. Too high or too low a ratio of aldehyde molecules to amino molecules will cause the COF crystals to fail to form; the concentration of glacial acetic acid will affect the particle size of COF crystals. When applied to a metal negative electrode, a particle size that is too large or too small will affect the dispersion of COF on the metal negative electrode and affect the battery performance.
[0023] As a preferred embodiment, the method further includes the following steps: adding the aldehyde molecules and the amino molecules to the first solvent, then dripping the glacial acetic acid, ultrasonically treating after the dripping is complete, then vacuumizing, heating to perform Schiff base polymerization reaction, and filtering, washing and vacuum drying after the reaction is complete.
[0024] As a preferred solution, the reaction temperature of the Schiff base polymerization is 100-150°C, the reaction time is 72-120h; the ultrasonic treatment time is 10-30min. If the reaction temperature is too low, COF crystals are difficult to form, and if it is too high, the COF crystal structure will be destroyed; if the reaction time is too long or too short, the crystal form will deteriorate.
[0025] Part III:
[0026] A metal secondary battery composite negative electrode is prepared from the functionalized covalent organic framework material described in the first aspect, or prepared from the functionalized covalent organic framework material obtained by the preparation method of the functionalized covalent organic framework material described in the second aspect.
[0027] Part 4:
[0028] A method for preparing a composite negative electrode for a metal secondary battery as described in the third part comprises the following steps:
[0029] dispersing the functionalized covalent organic framework material in a second solvent to obtain a mixed solution;
[0030] Dropping the mixed solution onto the metal, heating to volatilize the second solvent, and obtaining the metal secondary battery composite negative electrode;
[0031] The second solvent includes at least one of ethylene glycol dimethyl ether, 1,4-dioxane, 1,3-dioxolane, methanol, and N-methylpyrrolidone; and the metal includes at least one of lithium, sodium, potassium, and zinc.
[0032] As a preferred embodiment, the liquid-to-solid ratio of the second solvent to the functionalized covalent organic framework material is 1-3 mL:1 mg; the metal is a sheet metal; and the drop coating amount of the mixed solution on the sheet metal is 0.17-0.28 μL / mm 2 The heating temperature for volatilizing the second solvent is 40 to 80°C, and the heating time is 4 to 12 hours.
[0033] Part V:
[0034] A metal secondary metal battery comprises the metal secondary battery composite negative electrode described in the third part, or the metal secondary battery composite negative electrode obtained by the preparation method of the metal secondary battery composite negative electrode described in the fourth part. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 TEM image of the functionalized covalent organic framework material prepared in Example 1;
[0036] Figure 2 This is the nitrogen adsorption-desorption curve of the functionalized covalent organic framework material prepared in Example 1;
[0037] Figure 3 The pore size distribution of the functionalized covalent organic framework material prepared in Example 1;
[0038] Figure 4 This is the XRD pattern of the functionalized covalent organic framework material prepared in Example 1. DETAILED DESCRIPTION
[0039] 1. A functionalized covalent organic framework material, the structural formula of which is shown in Formula I:
[0040]
[0041] Wherein, X is C and / or N, and Y includes at least one of dimethyl ether, 1,2-dimethoxyethyl, 1-methoxy-2-(2-methoxyethoxy)ethyl, 1-methoxy-2-methylpropane, 1-methoxybutane and 1-methoxyheptane (whose structural formulas are respectively ).
[0042] 2. Preparation of a functionalized covalent organic framework material
[0043] Adding aldehyde molecules and amino molecules to a first solvent, then dripping glacial acetic acid, ultrasonically treating for 10 to 30 minutes after the dripping is complete, then vacuumizing, heating to 100 to 150° C. for reaction for 72 to 120 hours, and performing Schiff base polymerization reaction. After the reaction is completed, filtering, washing with acetone and tetrahydrofuran, and vacuum drying are performed to obtain the functionalized covalent organic framework material;
[0044] The aldehyde group molecule includes at least one of 1,3,5-tris(p-formylphenyl)benzene and 2,4,6-tris(4-formylphenyl)-1,3,5-triazine;
[0045] The amino molecules include at least one of 2,5-dimethoxyterephthaloyl hydrazide, 2,5-bis(2-methoxyethoxy)terephthaloyl hydrazide, 2,5-bis(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)terephthaloyl hydrazide, 2,5-diisobutoxyterephthaloyl hydrazide, 2,5-dibutoxyterephthaloyl hydrazide, and 2,5-bis(heptyloxy)terephthaloyl hydrazide;
[0046] The first solvent includes at least one of mesitylene, 1,4-dioxane, o-dichlorobenzene, n-butanol, methanol, pyridine, N-methylpyrrolidone, and dimethyl sulfoxide.
[0047] The molar ratio of the aldehyde molecules to the amino molecules is 2:3-3.2, and the concentration of the glacial acetic acid is 6-12 mol / L; the liquid-solid ratio of the first solvent to the sum of the masses of the aldehyde molecules and the amino molecules is 1-2 mL:20 mg, and the volume ratio of the first solvent to the glacial acetic acid is 1:0.1-0.2.
[0048] 3. Preparation of composite negative electrode for metal secondary battery
[0049] uniformly dispersing the functionalized covalent organic framework material in a second solvent to obtain a mixed solution;
[0050] In a glove box (water and oxygen values <0.01ppm), the mixed solution is drop-coated on a lithium metal sheet (a lithium metal sheet is taken as an example in the embodiment of the present invention to facilitate the preparation of a symmetrical battery), and the drop-coated lithium metal sheet is heated on a heating table at 40-80°C for 4-12h to evaporate the second solvent. After cooling to room temperature, a metal secondary battery composite negative electrode is obtained, which is then cut and prepared into a pole piece with a diameter of 15mm.
[0051] The second solvent includes at least one of ethylene glycol dimethyl ether, 1,4-dioxane, 1,3-dioxolane, methanol, and N-methylpyrrolidone.
[0052] The liquid-to-solid ratio of the second solvent and the functionalized covalent organic framework material is 1-3 mL:1 mg; the drop coating amount of the mixed solution on the sheet metal is 0.17-0.28 μL / mm 2 .
[0053] 4. Preparation of Li||Li symmetric battery
[0054] The metal secondary battery composite negative electrode is used as a counter electrode and a working electrode (lithium metal sheet) to assemble a Li||Li symmetrical battery, the button battery model is CR2032, the separator is a polypropylene microporous membrane Celgard 2400, and the electrolyte is 1 mol / L LiTFSI (lithium bistrifluoromethylsulfonyl imide) / DOL (1,3-dioxolane) + DME (ethylene glycol dimethyl ether), wherein V / V=1:1.
[0055] 5. Preparation of lithium iron phosphate metal secondary battery
[0056] According to the mass ratio of 8:1:1, lithium iron phosphate, superconducting carbon black (Super P) conductive agent and polyvinylidene fluoride (PVDF) binder were weighed and mixed, and then 19 times the mass of PVDF N-methylpyrrolidone (NMP) was added, and the mixture was fully stirred into a paste, and then coated on the current collector aluminum foil with a scraper, and then placed in a 60°C vacuum drying oven for 8h, and cut into a 15mm diameter pole piece, and an active material loading of 4mg pole piece was obtained as a metal secondary battery positive electrode. Then the metal secondary battery positive electrode and the above-mentioned metal secondary battery composite negative electrode were transferred to a glove box filled with argon gas for assembly of button batteries. The button battery model was CR2032, the diaphragm was a polypropylene microporous membrane Celgard 2400, and the electrolyte was 1mol / L LiPF6 (lithium hexafluorophosphate) / EC (ethylene carbonate) + DMC (dimethyl carbonate) + EMC (ethyl methyl phosphate), where V / V / V=1:1:1.
[0057] Example 1
[0058] 1. Synthesis of functionalized covalent organic framework materials
[0059] 78.086 mg (0.2 mmol) of 1,3,5-tri(p-formylphenyl)benzene and 76.275 mg (0.3 mmol) of 2,5-dimethoxyterephthaloylhydrazide were weighed and mixed in 8 mL of n-butanol, and then 0.2 mL of 6 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 10 min, vacuum cycle degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the functionalized covalent organic framework material was obtained by filtration, washing with acetone and tetrahydrofuran, and vacuum drying.
[0060] 2. Preparation of composite negative electrode for metal secondary battery
[0061] Weigh 10 mg of the functionalized covalent organic framework material and evenly disperse it in 10 mL of N-methylpyrrolidone to obtain a mixed solution. In a glove box (water and oxygen values <0.01 ppm), take 30 μL of the mixed solution and drop it on a lithium metal sheet with a diameter of 15 mm. Place the drop-coated lithium metal sheet on a heating table and heat it at 60° C. for 6 h to evaporate the solvent. After cooling to room temperature, obtain a metal secondary battery composite negative electrode.
[0062] 3. Preparation of Li||Li symmetric battery
[0063] The metal secondary battery composite negative electrode is used as a counter electrode and a working electrode (lithium metal sheet) to assemble a Li||Li symmetrical battery, the button battery model is CR2032, the separator is a polypropylene microporous membrane Celgard 2400, and the electrolyte is 1 mol / L LiTFSI (lithium bistrifluoromethylsulfonyl imide) / DOL (1,3-dioxolane) + DME (ethylene glycol dimethyl ether), wherein V / V=1:1.
[0064] 4. Preparation of lithium iron phosphate metal secondary battery
[0065] According to the mass ratio of 8:1:1, lithium iron phosphate, superconducting carbon black (Super P) conductive agent and polyvinylidene fluoride (PVDF) binder were weighed and mixed, and then N-methylpyrrolidone (NMP) with a mass of 19 times of PVDF was added, and the mixture was fully stirred into a paste, and coated on the current collector aluminum foil with a scraper, and then placed in a vacuum drying oven at 60°C for 8 hours, and cut to prepare a pole piece with a diameter of 15 mm, and a pole piece with an active material load of 4 mg was obtained as a metal secondary battery positive electrode. Then the metal secondary battery positive electrode and the above-mentioned metal secondary battery composite negative electrode were transferred to a glove box filled with argon gas for assembly of button batteries. The button battery model was CR2032, the diaphragm was a polypropylene microporous membrane Celgard 2400, and the electrolyte was 1 mol / L LiPF6 (lithium hexafluorophosphate) / EC (ethylene carbonate) + DMC (dimethyl carbonate) + EMC (ethyl methyl phosphate), where V / V / V=1:1:1.
[0066] like Figure 1 As shown, transmission electron microscopy (TEM) shows that the functionalized covalent organic framework material is in the form of sheets.
[0067] like Figure 2 As shown, the Brunauer-Emmet-Teller (BET) method was used to analyze the adsorption-desorption curve and calculate the specific surface area of the sample; Figure 3 As shown, the pore size distribution curve is obtained by analyzing the desorption curve using the Barrett-Joyner-Halenda (BJH) method. Figure 2-3 It can be seen that the functionalized covalent organic framework material prepared in Example 1 has a large specific surface area (194.4331m 2 ·g -1 ) and the pore size distribution is mainly mesopores around 10nm. Thanks to its porous functionalized structure, it provides the basic conditions for accelerating ion mass transfer and improving electrochemical performance.
[0068] like Figure 4 As shown, it can be seen from X-ray diffraction (XRD) that around 3 degrees corresponds to the (001) characteristic peak of COF, proving the successful synthesis of COF.
[0069] Example 2
[0070] 1. Synthesis of functionalized covalent organic framework materials
[0071] 78.086 mg (0.2 mmol) of 1,3,5-tri(p-formylphenyl)benzene and 76.275 mg (0.3 mmol) of 2,5-dimethoxyterephthaloylhydrazide were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 6 mol / L glacial acetic acid was added dropwise, ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the mixture was filtered, washed with acetone and tetrahydrofuran, and vacuum dried to obtain a functionalized covalent organic framework material;
[0072] 2. Preparation of composite negative electrode for metal secondary battery
[0073] Weigh 10 mg of the functionalized covalent organic framework material and evenly disperse it in 10 mL of ethylene glycol dimethyl ether to obtain a mixed solution. In a glove box (water and oxygen values <0.01 ppm), take 45 μL of the mixed solution and drop it on a lithium metal sheet with a diameter of 15 mm. Place the drop-coated lithium metal sheet on a heating table and heat it at 40°C for 12 h to evaporate the solvent. After cooling to room temperature, obtain a metal secondary battery composite negative electrode.
[0074] 3. Preparation of Li||Li symmetric battery
[0075] The preparation method is the same as that of Example 1.
[0076] 4. Preparation of lithium iron phosphate metal secondary battery
[0077] The preparation method is the same as that of Example 1.
[0078] Example 3
[0079] 1. Synthesis of functionalized covalent organic framework materials
[0080] 78.086 mg (0.2 mmol) of 1,3,5-tri(p-formylphenyl)benzene and 129.138 mg (0.3 mmol) of 2,5-bis(2-(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)terephthaloylhydrazide) were weighed separately and mixed in 11 mL of n-butanol, and then 1.1 mL of 6 mol / L glacial acetic acid was added dropwise, and the mixture was ultrasonically treated for 20 min, vacuum-circulated for degassing, and heated at 100 ° C for 120 h to perform Schiff base polymerization reaction. After the reaction was completed, the mixture was filtered, washed with acetone and tetrahydrofuran, and vacuum-dried to obtain a functionalized covalent organic framework material;
[0081] 2. Preparation of composite negative electrode for metal secondary battery
[0082] Weigh 10 mg of the functionalized covalent organic framework material and evenly disperse it in 20 mL of 1,4-dioxane to obtain a mixed solution. In a glove box (water and oxygen values <0.01 ppm), take 49 μL of the mixed solution and drop it on a lithium metal sheet with a diameter of 15 mm. Place the drop-coated lithium metal sheet on a heating table and heat it at 80°C for 4 hours to evaporate the solvent. After cooling to room temperature, obtain a metal secondary battery composite negative electrode.
[0083] 3. Preparation of Li||Li symmetric battery
[0084] The preparation method is the same as that of Example 1.
[0085] 4. Preparation of lithium iron phosphate metal secondary battery
[0086] The preparation method is the same as that of Example 1.
[0087] Example 4
[0088] 1. Synthesis of functionalized covalent organic framework materials
[0089] 78.086 mg (0.2 mmol) of 1,3,5-tri(p-formylphenyl)benzene and 101.523 mg (0.3 mmol) of 2,5-diisobutyloxyterephthaloylhydrazide were weighed and mixed in 9 mL of n-butanol, and then 0.9 mL of 6 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 30 min, vacuum cycle degassing was performed, and Schiff base polymerization was performed at 150° C. for 90 h. After the reaction was completed, the functionalized covalent organic framework material was obtained by filtration, washing with acetone and tetrahydrofuran, and vacuum drying.
[0090] 2. Preparation of composite negative electrode for metal secondary battery
[0091] Weigh 10 mg of the functionalized covalent organic framework material and evenly disperse it in 30 mL of 1,3-dioxolane to obtain a mixed solution. In a glove box (water and oxygen values <0.01 ppm), take 30 μL of the mixed solution and drop it on a lithium metal sheet with a diameter of 15 mm. Place the drop-coated lithium metal sheet on a heating table and heat it at 60° C. for 12 h to evaporate the solvent. After cooling to room temperature, obtain a metal secondary battery composite negative electrode.
[0092] 3. Preparation of Li||Li symmetric battery
[0093] The preparation method is the same as that of Example 1.
[0094] 4. Preparation of lithium iron phosphate metal secondary battery
[0095] The preparation method is the same as that of Example 1.
[0096] Example 5
[0097] 1. Synthesis of functionalized covalent organic framework materials
[0098] 78.086 mg (0.2 mmol) of 1,3,5-tri(p-formylphenyl)benzene and 101.523 mg (0.3 mmol) of 2,5-diisobutyloxyterephthaloylhydrazide were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 12 mol / L glacial acetic acid was added dropwise, ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the mixture was filtered, washed with acetone and tetrahydrofuran, and dried in vacuum to obtain a functionalized covalent organic framework material;
[0099] 2. Preparation of composite negative electrode for metal secondary battery
[0100] The preparation method is the same as that of Example 1.
[0101] 3. Preparation of Li||Li symmetric battery
[0102] The preparation method is the same as that of Example 1.
[0103] 4. Preparation of lithium iron phosphate metal secondary battery
[0104] The preparation method is the same as that of Example 1.
[0105] Example 6
[0106] 1. Synthesis of functionalized covalent organic framework materials
[0107] 78.086 mg (0.2 mmol) of 1,3,5-tri(p-formylphenyl)benzene and 126.771 mg (0.3 mmol) of 2,5-bis(heptyloxy)terephthaloylhydrazide were weighed and mixed in 11 mL of n-butanol, and then 1.1 mL of 9 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the mixture was filtered, washed with acetone and tetrahydrofuran, and dried in vacuum to obtain a functionalized covalent organic framework material;
[0108] 2. Preparation of composite negative electrode for metal secondary battery
[0109] The preparation method is the same as that of Example 1.
[0110] 3. Preparation of Li||Li symmetric battery
[0111] The preparation method is the same as that of Example 1.
[0112] 4. Preparation of lithium iron phosphate metal secondary battery
[0113] The preparation method is the same as that of Example 1.
[0114] Example 7
[0115] 1. Synthesis of functionalized covalent organic framework materials
[0116] 78.678 mg (0.2 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 76.275 mg (0.3 mmol) of 2,5-dimethoxyterephthaloylhydrazide were weighed and mixed in 8 mL of n-butanol, and then 0.8 mL of 6 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the functionalized covalent organic framework material was obtained by filtration, washing with acetone and tetrahydrofuran, and vacuum drying.
[0117] 2. Preparation of composite negative electrode for metal secondary battery
[0118] The preparation method is the same as that of Example 1.
[0119] 3. Preparation of Li||Li symmetric battery
[0120] The preparation method is the same as that of Example 1.
[0121] 4. Preparation of lithium iron phosphate metal secondary battery
[0122] The preparation method is the same as that of Example 1.
[0123] Example 8
[0124] 1. Synthesis of functionalized covalent organic framework materials
[0125] 78.678 mg (0.2 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 102.705 mg (0.3 mmol) of 2,5-bis(2-methoxyethoxy)terephthaloylhydrazide were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 6 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the functionalized covalent organic framework material was obtained by filtration, washing with acetone and tetrahydrofuran, and vacuum drying.
[0126] 2. Preparation of composite negative electrode for metal secondary battery
[0127] The preparation method is the same as that of Example 1.
[0128] 3. Preparation of Li||Li symmetric battery
[0129] The preparation method is the same as that of Example 1.
[0130] 4. Preparation of lithium iron phosphate metal secondary battery
[0131] The preparation method is the same as that of Example 1.
[0132] Example 9
[0133] 1. Synthesis of functionalized covalent organic framework materials
[0134] 78.678 mg (0.2 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 129.138 mg (0.3 mmol) of 2,5-bis(2-(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)terephthaloylhydrazide) were weighed separately and mixed in 11 mL of n-butanol, and then 1.1 mL of 6 mol / L glacial acetic acid was added dropwise, and the mixture was ultrasonically treated for 10 min, vacuum-cycled degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the mixture was filtered, washed with acetone and tetrahydrofuran, and vacuum-dried to obtain a functionalized covalent organic framework material;
[0135] 2. Preparation of composite negative electrode for metal secondary battery
[0136] The preparation method is the same as that of Example 1.
[0137] 3. Preparation of Li||Li symmetric battery
[0138] The preparation method is the same as that of Example 1.
[0139] 4. Preparation of lithium iron phosphate metal secondary battery
[0140] The preparation method is the same as that of Example 1.
[0141] Example 10
[0142] 1. Synthesis of functionalized covalent organic framework materials
[0143] 78.678 mg (0.2 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 101.523 mg (0.3 mmol) of 2,5-diisobutyloxyterephthaloylhydrazide were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 6 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the functionalized covalent organic framework material was obtained by suction filtration, washing with acetone and tetrahydrofuran, and vacuum drying.
[0144] 2. Preparation of composite negative electrode for metal secondary battery
[0145] The preparation method is the same as that of Example 1.
[0146] 3. Preparation of Li||Li symmetric battery
[0147] The preparation method is the same as that of Example 1.
[0148] 4. Preparation of lithium iron phosphate metal secondary battery
[0149] The preparation method is the same as that of Example 1.
[0150] Embodiment 11
[0151] 1. Synthesis of functionalized covalent organic framework materials
[0152] 78.678 mg (0.2 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 101.523 mg (0.3 mmol) of 2,5-dibutoxyterephthaloylhydrazide were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 6 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the functionalized covalent organic framework material was obtained by suction filtration, washing with acetone and tetrahydrofuran, and vacuum drying.
[0153] 2. Preparation of composite negative electrode for metal secondary battery
[0154] The preparation method is the same as that of Example 1.
[0155] 3. Preparation of Li||Li symmetric battery
[0156] The preparation method is the same as that of Example 1.
[0157] 4. Preparation of lithium iron phosphate metal secondary battery
[0158] The preparation method is the same as that of Example 1.
[0159] Example 12
[0160] 1. Synthesis of functionalized covalent organic framework materials
[0161] 78.678 mg (0.2 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 126.771 mg (0.3 mmol) of 2,5-bis(heptyloxy)terephthaloylhydrazide were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 6 mol / L glacial acetic acid was added dropwise, and ultrasonic treatment was performed for 10 min, vacuum circulation degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, the mixture was filtered, washed with acetone and tetrahydrofuran, and vacuum dried to obtain a functionalized covalent organic framework material;
[0162] 2. Preparation of composite negative electrode for metal secondary battery
[0163] The preparation method is the same as that of Example 1.
[0164] 3. Preparation of Li||Li symmetric battery
[0165] The preparation method is the same as that of Example 1.
[0166] 4. Preparation of lithium iron phosphate metal secondary battery
[0167] The preparation method is the same as that of Example 1.
[0168] Comparative Example 1
[0169] In this comparative example, a lithium metal sheet is directly used as the negative electrode of the metal secondary battery.
[0170] 1. Preparation of Li||Li symmetric battery
[0171] A Li||Li symmetric battery was assembled using a lithium metal sheet as the counter electrode and the working electrode. The button cell model was CR2032, the separator was a polypropylene microporous membrane Celgard 2400, and the electrolyte was 1 mol / L LiTFSI / DOL+DME (V / V=1:1).
[0172] 2. Preparation of lithium iron phosphate metal secondary battery
[0173] Lithium iron phosphate, superconducting carbon black conductive agent and polyvinylidene fluoride binder were weighed and mixed according to a mass ratio of 8:1:1, and then N-methylpyrrolidone with a mass of 19 times that of PVDF was added, and the mixture was fully stirred into a paste. The mixture was coated on the current collector aluminum foil with a scraper, and then placed in a vacuum drying oven at 60°C for 8 hours, and cut to prepare a pole piece with a diameter of 15 mm, and a pole piece with an active material load of 4 mg was obtained as the positive electrode of the metal secondary battery. Then the positive electrode of the metal secondary battery and the negative electrode of the lithium metal sheet were transferred to a glove box filled with argon gas for assembly of a button battery. The button battery model was CR2032, the diaphragm was a polypropylene microporous membrane Celgard 2400, and the electrolyte was 1 mol / L LiPF6 / EC+DMC+EMC (V / V / V=1:1:1).
[0174] Comparative Example 2
[0175] 1. Synthesis of Schiff base porous organic polymers
[0176] 78.086 mg (0.2 mmol) of 1,3,5-tri(p-formylphenyl)benzene and 58.257 mg (0.3 mmol) of terephthalic acid dihydrazine were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 6 mol / L glacial acetic acid was added dropwise, ultrasonic treatment was performed for 10 min, vacuum cycle degassing was performed, and Schiff base polymerization was performed at 120°C for 72 h. After the reaction was completed, the mixture was filtered, washed with acetone and tetrahydrofuran, and vacuum dried to obtain a Schiff base type porous organic polymer;
[0177] 2. Preparation of composite negative electrode for metal secondary battery
[0178] Weigh 10 mg of Schiff base porous organic polymer and evenly disperse it in 10 mL of N-methylpyrrolidone to obtain a mixed solution. In a glove box (water and oxygen values <0.01 ppm), take 30 μL of the mixed solution and drop it on a lithium metal sheet with a diameter of 15 mm. Place the drop-coated lithium metal sheet on a heating table and heat it at 60°C for 6 h to evaporate the solvent. After cooling to room temperature, obtain a metal secondary battery composite negative electrode.
[0179] 3. Preparation of Li||Li symmetric battery
[0180] The preparation method is the same as that of Example 1.
[0181] 4. Preparation of lithium iron phosphate metal secondary battery
[0182] The preparation method is the same as that of Example 1.
[0183] Comparative Example 3
[0184] 1. Synthesis of Schiff base porous organic polymers
[0185] 78.678 mg (0.2 mmol) of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine and 58.257 mg (0.3 mmol) of terephthalic acid dihydrazine were weighed and mixed in 10 mL of n-butanol, and then 1 mL of 6 mol / L glacial acetic acid was added dropwise, ultrasonic treatment was performed for 10 min, vacuum cycle degassing was performed, and Schiff base polymerization was performed at 120° C. for 72 h. After the reaction was completed, suction filtration, acetone and tetrahydrofuran washing, and vacuum drying were performed to obtain a Schiff base type porous organic polymer;
[0186] 2. Preparation of composite negative electrode for metal secondary battery
[0187] Weigh 10 mg of Schiff base porous organic polymer and evenly disperse it in 10 mL of N-methylpyrrolidone to obtain a mixed solution. In a glove box (water and oxygen values <0.01 ppm), take 30 μL of the mixed solution and drop it on a lithium metal sheet with a diameter of 15 mm. Place the drop-coated lithium metal sheet on a heating table and heat it at 60°C for 6 h to evaporate the solvent. After cooling to room temperature, obtain a metal secondary battery composite negative electrode.
[0188] 3. Preparation of Li||Li symmetric battery
[0189] The preparation method is the same as that of Example 1.
[0190] 4. Preparation of lithium iron phosphate metal secondary battery
[0191] The preparation method is the same as that of Example 1.
[0192] Effect verification
[0193] 1. Pore distribution test of functionalized covalent organic framework materials
[0194] The functionalized covalent organic framework material prepared in Example 1 was used for pore distribution test. Specifically, the nitrogen adsorption-desorption curve of the metal-doped covalent organic framework material was tested at a temperature of 77 K using a BELSORP-mini device. Figure 2 The Brunauer-Emmet-Teller (BET) method was used to analyze the adsorption-desorption curve and calculate the specific surface area of the sample. In addition, the Barrett-Joyner-Halenda (BJH) method was used to analyze the desorption curve and obtain the pore size distribution curve, as shown in Figure 3 As shown. Figure 2-3 It can be seen that the functionalized covalent organic framework material prepared in Example 1 has a large specific surface area (194.4331m 2 ·g -1 ) and the pore size distribution is mainly mesopores of about ten nanometers. Thanks to its porous functionalized structure, it provides the basic conditions for accelerating ion mass transfer and improving electrochemical performance.
[0195] 2. Young's modulus test of functionalized covalent organic framework materials
[0196] The functionalized covalent organic framework material prepared in Example 1 was tested by an RTESP-525 atomic force microscope (AFM, Bruker Demension Icon) equipped with a silicon probe, and the surface Young's modulus was analyzed by the Derjaguin-Muller-Toporov (DMT) module of NanoScope Analysis to obtain a surface Young's modulus of 18 GPa. Good mechanical properties can alleviate the growth of dendrites.
[0197] 3. Electrochemical performance test of Li||Li symmetric battery
[0198] The Li||Li symmetrical batteries prepared in Examples 1-12 and Comparative Examples 1-3 were subjected to electrochemical performance tests on a Xinwei test system at a test condition of 1 mA / cm 2 , 1mAh / cm 2 , the test results are shown in Table 1.
[0199] Table 1 Electrochemical performance test results of Li||Li symmetric battery
[0200]
[0201] As can be seen from Table 1, the Li||Li symmetric battery assembled in the embodiment of the present invention has lower nucleation overpotential, polarization voltage and longer cycle life than the Li||Li symmetric battery assembled in the comparative example. The performance of Examples 1-6 and Examples 7-12 is improved as the length of the side chain group increases. Comparative Examples 2 and 3 use amino molecules without side chain groups, and Comparative Example 3 has improved performance compared to Comparative Example 2 because the triazine structure of the aldehyde monomer can serve as a site to attract cations and accelerate cation transport.
[0202] 4. Electrochemical performance test of lithium iron phosphate metal secondary battery
[0203] The lithium iron phosphate metal secondary batteries prepared in Examples 1-12 and Comparative Examples 1-3 were subjected to electrochemical performance tests on a Xinwei test system. The test voltage range was 2.4-4.2V. The test results are shown in Table 2.
[0204] Table 2 Electrochemical performance test results of lithium iron phosphate metal secondary batteries
[0205]
[0206]
[0207] As can be seen from Table 2, the lithium iron phosphate metal secondary battery assembled in the embodiment of the present invention has a significantly improved first-cycle discharge specific capacity and capacity retention rate compared to the lithium iron phosphate metal secondary battery assembled in the comparative example. Among them, as the length of the side chain group increases, the capacity retention rate of Examples 1-6 and Examples 7-12 is improved, which is attributed to the increase in the cation transmission rate, which alleviates the growth of metal dendrites and reduces the capacity loss caused by dendrite breakage. Comparative Examples 2 and 3 use amino molecules without side chain groups, and Comparative Example 3 has improved performance compared to Comparative Example 2 because the triazine structure of the aldehyde monomer can be used as a site to attract cations to increase the transmission rate.
[0208] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A functionalized covalent organic framework material, characterized in that: The structural formula is shown in Formula I: Wherein, X is C and / or N, and Y includes at least one of dimethyl ether, 1,2-dimethoxyethyl, 1-methoxy-2-(2-methoxyethoxy)ethyl, 1-methoxy-2-methylpropane, 1-methoxybutane and 1-methoxyheptane.
2. A method for preparing the functionalized covalent organic framework material according to claim 1, characterized in that: The steps include: Mixing aldehyde molecules, amino molecules, glacial acetic acid and a first solvent, and heating to react to obtain the functionalized covalent organic framework material; The aldehyde group molecule includes at least one of 1,3,5-tris(p-formylphenyl)benzene and 2,4,6-tris(4-formylphenyl)-1,3,5-triazine; The amino molecules include at least one of 2,5-dimethoxyterephthaloyl hydrazide, 2,5-bis(2-methoxyethoxy)terephthaloyl hydrazide, 2,5-bis(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)terephthaloyl hydrazide, 2,5-diisobutoxyterephthaloyl hydrazide, 2,5-dibutoxyterephthaloyl hydrazide, and 2,5-bis(heptyloxy)terephthaloyl hydrazide; The first solvent includes at least one of mesitylene, 1,4-dioxane, o-dichlorobenzene, n-butanol, methanol, pyridine, N-methylpyrrolidone, and dimethyl sulfoxide.
3. The method for preparing a functionalized covalent organic framework material according to claim 2, characterized in that: The molar ratio of the aldehyde molecules to the amino molecules is 2:3-3.2, and the concentration of the glacial acetic acid is 6-12 mol / L; the liquid-solid ratio of the first solvent to the sum of the masses of the aldehyde molecules and the amino molecules is 1-2 mL:20 mg, and the volume ratio of the first solvent to the glacial acetic acid is 1:0.1-0.
2.
4. The method for preparing a functionalized covalent organic framework material according to claim 2, characterized in that: The aldehyde molecules and the amino molecules are added to the first solvent, and then the glacial acetic acid is added dropwise. After the addition is completed, ultrasonic treatment is performed, and then vacuumization is performed and heating is performed to perform Schiff base polymerization reaction. After the reaction is completed, suction filtration, washing and vacuum drying are performed.
5. The method for preparing a functionalized covalent organic framework material according to claim 4, characterized in that: The reaction temperature of the Schiff base polymerization is 100-150° C., and the reaction time is 72-120 hours; the time of the ultrasonic treatment is 10-30 minutes.
6. A metal secondary battery composite negative electrode, characterized in that: The functionalized covalent organic framework material is prepared from the functionalized covalent organic framework material according to claim 1, or the functionalized covalent organic framework material is prepared from the functionalized covalent organic framework material obtained by the preparation method of the functionalized covalent organic framework material according to any one of claims 2 to 5.
7. A method for preparing a composite negative electrode for a metal secondary battery as claimed in claim 6, characterized in that: The method comprises the following steps: dispersing the functionalized covalent organic framework material in a second solvent to obtain a mixed solution; Dropping the mixed solution onto the metal, heating to volatilize the second solvent, and obtaining the metal secondary battery composite negative electrode; The second solvent includes at least one of ethylene glycol dimethyl ether, 1,4-dioxane, 1,3-dioxolane, methanol, and N-methylpyrrolidone; and the metal includes at least one of lithium, sodium, potassium, and zinc.
8. The method for preparing a composite negative electrode for a metal secondary battery according to claim 7, characterized in that: The liquid-to-solid ratio of the second solvent and the functionalized covalent organic framework material is 1-3 mL:1 mg; the metal is a sheet metal; the drop coating amount of the mixed solution on the sheet metal is 0.17-0.28 μL / mm 2 The heating temperature for volatilizing the second solvent is 40 to 80°C, and the heating time is 4 to 12 hours.
9. A metal secondary metal battery, characterized in that: The invention comprises the metal secondary battery composite negative electrode as claimed in claim 6, or the metal secondary battery composite negative electrode obtained by the preparation method of the metal secondary battery composite negative electrode as claimed in any one of claims 7 to 8.
Citation Information
Patent Citations
Application of covalent organic framework material in lithium metal negative electrode protection
CN112993256A
Preparation method and application of zinc negative electrode modified by covalent organic framework material
CN113725421A